2018
DOI: 10.2147/ijnrd.s162230
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic kidney disease in Nigeria: systematic review of population-based studies

Abstract: BackgroundThe aim of this study was to identify and discuss published population-based studies carried out in Nigeria that have information on the prevalence of chronic kidney disease (CKD) and have also used the Kidney Disease Outcomes Quality Initiative (KDOQI) practice guidelines in defining CKD, with emphasis on the performance of three estimating equations for glomerular filtration rate (GFR) – Modification of Diet in Renal Disease (MDRD), Cock-croft–Gault, and CKD epidemiology collaboration (CKD-EPI) cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 28 publications
8
37
0
Order By: Relevance
“…Chronic kidney disease (CKD) is a global public health problem (1,2), that increasing rapidly worldwide and is gaining much attention in both the developed as well as developing countries (3,4). It is found in 10% of the global population (5,6), and it affects 10-16% of the adult population in China, Asia, Australia, Europe and the United States (7).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic kidney disease (CKD) is a global public health problem (1,2), that increasing rapidly worldwide and is gaining much attention in both the developed as well as developing countries (3,4). It is found in 10% of the global population (5,6), and it affects 10-16% of the adult population in China, Asia, Australia, Europe and the United States (7).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of CKD in Nigeria is 11.4-26% [13]. Hypertension is a major cause of CKD and chronic renal failure (CRF) in Nigeria.…”
Section: Check For Updatesmentioning
confidence: 99%
“…There is no national data on prevalence of CKD, and only few community-based studies were done in some regions of the country. A recent systematic review identified 7 population-based studies, 5 from the Southern part and 2 from the Northern part [ 5 ]; in this study, the prevalence of CKD ranged from 2.5 to 26%. Oluyombo et al [ 6 ] previously reported the prevalence of CKD of 18% in a rural community in South-Western Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Similar study in the South-East Nigeria found a prevalence of 11.4% in rural, and 11.7% in semi-urban dwellers [ 7 ]. In addition, a study from North-West Nigeria in the recent review documented CKD prevalence of 26% [ 5 ], suggesting overall high prevalence of CKD and indicating a need for more studies to understand the true burden of CKD in Nigerian population. Combining regional population-based studies with sufficient power allow to estimate the true magnitude of CKD where national data is lacking.…”
Section: Introductionmentioning
confidence: 99%